A lei de execução penal e as políticas de assistência ao apenado : um estudo sobre a Penitenciária Industrial de Guarapuava - Scheidt, Joelma Marcela (2014)
The penitentiary system was born with the function of collecting and hiding the ills from the practice of expropriation-exploration of different economic models. In Brazil the law 7,210/1984 Law of Penal Execution-LEP, aimed to overcome a major challenge in modifying the old paradigm of prison-punishment conceived as mere humans deposit devoid of any essential right to human dignity. According to this Law, the State is appointed as the protagonist in the formulation and execution of public politics aimed at the improvement of the penal execution process and to guarantee the rights of person arrested and should be responsible for the preparation and implementation of actions designed to promote improvement of prisons and the treatment offered to prisoners in Brazil. In spite of such guidelines, there are notorious dissonance between the purpose and the reality. The present study sought to discuss the social function of the privation of liberty sentence and their transformations throughout the story. The study addressed the advancement of the Penal State and the process of dismantling the welfare State, analyzing the politics of repression operated by the State in order to contain the social conflicts caused by the neoliberal model. It was analyzed during the work the way inmates assistance politics has been implemented nationally and in the State of Paraná. The main objective was to analyze the application of LEP on Industrial penitentiary of Guarapuava-PIG, prison unit located in the State of Paraná, devoted to seclusion of male convicts, whose history is marked by pioneering in Brazil by prioritize in offering remunerated work and education to sentenced, full-time. Elements regarded as fundamental to the process of social reintegration of inmates. Research, in qualitative character was performed by means of bibliographical and documentary research. Bibliographical references and documents were used and properly authorized and provided by the Secretary of Justice, citizenship and Human Rights of the State of Paraná ? SEJU on the penitentiary unity of Guarapuava, their regulations implementation and deployment and other related central theme of the present research. what is the social function of the privation of liberty sentence and the promotion of conditions of re-socialization of inmates as advocates the LEP during the execution of the sentence. The results showed that although LEP has nearly three decades of existence, little has changed in reality of the Brazilian prison system and that the first actions in the scope of public politics to perform the provisions of the legislation are relatively recent and are performed punctual and fragmented. On the context of weaknesses presented by most Brazilian prisons the PIG ended up highlighting the broad access of sentenced to job opportunities and education and the maintenance of the reduced number of sentenced collected, breaking with the logic of prison overcrowding in the prisons in Brazil. The study pointed out that the PIG away represents an advance in penal treatment model in Brazil, still has shortcomings and difficulties that are maintained on the grounds of gaps and misconceptions contained in the LEP and the frequent omission of State front their responsibility as protagonist of formulation and in guaranteeing the fundamental rights of the sentenced.